1999
DOI: 10.1046/j.1365-2885.1999.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption kinetics and bioavailability of cephalexin in the dog after oral and intramuscular administration

Abstract: The pharmacokinetics of cephalexin, a first generation cephalosporin, were investigated in dogs using two formulations marketed for humans, but also often employed by practitioners for pet therapy. Cephalexin was administered to five dogs intravenously and intramuscularly as a sodium salt and by the oral route as a monohydrate. The dosage was always 20 mg/kg of active ingredient. A microbiological assay with Sarcina lutea as the test organism was adopted to measure cephalexin concentrations in serum. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
3
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
8
16
3
3
Order By: Relevance
“…The pharmacokinetic parameters calculated in this study after the 10 : 00 h administration are similar to those previously reported by other authors after the oral administration of cephalexin to dogs (Campbell & Rosin, 1998;Carli et al, 1999;Crosse & Burt, 1984;Silley et al, 1988). A. P. Prados et al 166 This study further compared these pharmacokinetic parameters to those calculated after the 22 : 00 h administration in order to explore the hypothesis that absorption would be less and elimination slower when cephalexin was orally administered to dogs during the rest phase.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The pharmacokinetic parameters calculated in this study after the 10 : 00 h administration are similar to those previously reported by other authors after the oral administration of cephalexin to dogs (Campbell & Rosin, 1998;Carli et al, 1999;Crosse & Burt, 1984;Silley et al, 1988). A. P. Prados et al 166 This study further compared these pharmacokinetic parameters to those calculated after the 22 : 00 h administration in order to explore the hypothesis that absorption would be less and elimination slower when cephalexin was orally administered to dogs during the rest phase.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, C max was decreased significantly to almost 77% of its value after cephalexin was administered at nighttime, without varying the time during the 12 h dosing interval when peak concentration was obtained. PEPT1 mediates the intestinal absorption of cephalexin in rats, humans (Berlioz et al, 1999;Buyse et al, 2001;Ganapathy et al, 1995), and most probably dogs (Carli et al, 1999); additional mechanisms, such as passive diffusion, are of minor importance due to the low lipophilicity of the medication (Berlioz et al, 1999). Previous studies have demonstrated that the intestinal permeability of cephalexin is directly proportional to PEPT1 expression in Caco-2/hPEPT1 cells and in rat intestinal mucosa (Chu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This values is similar to that reported for dogs (60%) (Carli et al, 1999;Chicoine et al, After multiple administration bioavailability was higher (p<0.05), this difference could be reflecting the improvement of absorption when small volumes are injected (Zuidema et al, 1994).…”
Section: Resultssupporting
confidence: 89%
“…This is consequence of the high inter-animal variation observed, especially, after IV and single IM administration. The estimated valueswere similar to that in other species such as, rat (Tsai et al, 2000) dog (Carli et al, 1999) and cat (Albarellos et al, 2011). Accumulation index after multiple administrationswas closed to 1, reflecting cephalexin low accumulation capacity.Similar values are reported for humans after repeated oral administration (Pfeffer et al, 1977).…”
Section: Resultssupporting
confidence: 84%
“…As in this study for cefotaxime, cephalosporins seem to be rapidly cleared in dogs. Carli et al (1999) suggested a dose interval of 6 to 8 h for cephalexin after i.m. administration, but much faster elimination rates have been found (Schermerhorn et al, 1994).…”
Section: Discussionmentioning
confidence: 99%